Seismic Imaging of the Mw 7.1 Ridgecrest Earthquake Rupture Zone From Data Recorded by Dense Linear Arrays. Issue 7 (7th July 2021) - Qiu, Hongrui; Ben‐Zion, Yehuda; Catchings, Rufus; Goldman, Mark R.; Allam, Amir A.; Steidl, Jamison
Abstract: We analyze seismograms recorded by four arrays (B1–B4) with 100 m station spacing and apertures of 4–8 km that cross the surface rupture of the 2019 Mw 7.1 Ridgecrest earthquake. The arrays extend from B1 in the northwest to B4 in the southeast of the surface rupture. Delay times between P wave arrivals associated with ∼1, 200 local earthquakes and four teleseismic events are used to estimate local velocity variations beneath the arrays. Both teleseismic and local P waves travel faster on the northeast than the southwest side of the fault beneath arrays B1 and B4, but the velocity contrast is less reliably resolved at arrays B2 and B3. We identify several 1–2 km wide low‐velocity zones with much slower inner cores that amplify S waveforms, inferred as damage zones, beneath each array. The damage zones at arrays B2 and B4 also generate fault‐zone head and trapped waves. An automated detector, based on peak ground velocities and durations of high‐amplitude waves, identifies candidate fault‐zone trapped waves (FZTWs) in a localized zone for ∼600 earthquakes at array B4. Synthetic waveform modeling of averaged FZTWs, generated by ∼30 events with high‐quality signals, indicates that the trapping structure at array B4 has a width of ∼300 m, depth of 3–5 km, S wave velocity reduction of ∼20% with respect to the surrounding rock, Q ‐value of ∼30, and S wave velocity contrast of ∼4% across the fault (faster on the northeast side). The results show complex fault‐zone internal structures (velocity contrasts and low‐velocity zones) that vary along fault strike. Plain Language Summary: The 2019 Mw 7.1 Ridgecrest earthquake in the Eastern California Shear Zone generated a vigorous aftershock sequence that provided a wealth of seismic data. We derive subsurface structural properties within and across the Ridgecrest rupture zone from seismic waveforms generated by the earthquake sequence. The data are recorded by four dense nodal arrays that were deployed across the Ridgecrest rupture zone with ∼100 m spacing and aperture of a few kilometers. Delay times of P wave and amplification of S waves are used to infer on several 1–2 km wide low‐velocity zones with more intensely damaged inner cores (0.5–1.5 km wide) beneath each array. Waveform modeling of fault zone trapped waves well‐recorded by one array provides geometrical and seismic properties of a coherent waveguide in the damage fault zone structure at that location. The results are complementary to tomographic models that provide a regional context but do not resolve internal structural elements of the Ridgecrest rupture zone. Key Points: Several 1–2 km wide low‐velocity zones with more intensely damaged inner cores (0.5–1.5 km wide) are identified beneath each array An automated detector, based on peak ground velocities and durations of high amplitude S waves, identifies fault‐zone trapped waves The P wave delay time and S wave amplification patterns indicate consistent locations and widths of fault damage zones